2017
DOI: 10.1590/1517-869220172302153651
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos Do Treinamento Aeróbico E Do Fortalecimento Em Pacientes Com Insuficiência Cardíaca

Abstract: Introduction: Exercise intolerance and dyspnea are the main symptoms of heart failure (HF). Objective: To evaluate the effects of a program of aerobic exercises and strengthening on cardiorespiratory fitness, maximum torque of knee flexors and extensors, and quality of life of patients with HF. Methods: Prospective, pre-and post-cardiovascular rehabilitation (CVR) study of seven patients, aged 61 ± 6 years, functional class II and III and left ventricular ejection fraction 45.4 ± 2.3%. The CVR program consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
0
8
0
7
Order By: Relevance
“…14 Physical exercise influences physical fitness, whose components include flexibility, muscle strength, cardiorespiratory endurance and body composition. 15 The studies by Mandic et al, 16 and Calegari et al, 17 have shown that the regular practice of physical activity has favorable effects on the body composition and functional capacity of individuals with CVD. However, whether the VR intervention as a physical exercise modality has benefits similar to those of the cardiovascular rehabilitation process remains controversial.…”
Section: -629mentioning
confidence: 99%
“…14 Physical exercise influences physical fitness, whose components include flexibility, muscle strength, cardiorespiratory endurance and body composition. 15 The studies by Mandic et al, 16 and Calegari et al, 17 have shown that the regular practice of physical activity has favorable effects on the body composition and functional capacity of individuals with CVD. However, whether the VR intervention as a physical exercise modality has benefits similar to those of the cardiovascular rehabilitation process remains controversial.…”
Section: -629mentioning
confidence: 99%
“…De acordo com O' Connor et al (2009), Calegari et al (2017), Ogawa et al (2009) e Plentz et al (2012) a fisioterapia é extremamente relevante nestas situações, pois os profissionais dessa área são os responsáveis pela promoção da saúde desses pacientes. O presente estudo é uma revisão de literatura, foram utilizadas como fontes de pesquisa, as bases de dados: PubMed, Scielo, NHS Evidence Embase e LILACS, com período de publicação entre os anos de 2010 e 2019.…”
Section: Resultsunclassified
“…14 In this context, resistance training is an important complement to aerobic exercise to improve muscular strength, tolerance to the efforts, and quality of life. 3,5,7 Some limitations must be considered in this study. The small number of participants and the inclusion of women and men must be taken into consideration in the interpretation of our results, although other studies have used seven to nine individuals and evaluated the same variables.…”
Section: Discussionmentioning
confidence: 99%
“…1-,3 Muscle strengthening exercises can control risk factors such as obesity and insulin resistance, improve blood pressure, reduce peripheral vascular resistance, and optimize endothelial function [3][4][5] Resistance training promotes improvements in quality of life and functional capacity in patients with cardiac disease. 6,7 However, there are few studies about cardiovascular, metabolic, and ventilatory responses during strengthening exercises, using an isokinetic dynamometer in patients with coronary artery disease (CAD).…”
Section: Introductionmentioning
confidence: 99%